STONE INDUSTRY OF LEILATEPE CULTURE - Museibli, Nadzaf Alesker oglu (History, Archeology and Ethnography of the Caucasus, 2022)
One of the characteristic features of the Leilatepe culture of the Chalcolithic period (end of the 5th millennium BC – first half of the 4th millennium BC) is its unique stone industry. This archeological culture has been studied mainly on the basis of sites in the territory of Azerbaijan. Extensive excavations in Leilatepe, Beyuk Kesik I, Poylu II, Galayeri settlements belonging to the Leilatepe culture revealed numerous stone tools. Similar tools were also discovered as a result of short-term excavations carried out in residential areas of Agili Dere, Selakhan, and some others belonging to this culture. The discovered stone tools and their functional purpose gives us reasons to conclude that the bearers of this culture lived a sedentary life and were mainly engaged in agriculture and cattle breeding. Thus, during the excavations a large number of quern stones, graters, sickle teeth, etc., typical for early farming, made of different types of stones, were found. The explorations showed the prevalence of flint tools over obsidian products in all other sites belonging to the Leilatepe culture, except for the Galayeri settlement. Alongside with them, other tools and products made of stone – details of a potter’s wheel, mace heads, scepters, balance weights, etc. – were found in the sites of the abovementioned Leilatepe culture. The stone industry of the Leilatepe culture is closely related to the traditions of Eastern Anatolia and Northern Mesopotamia. At the same time, similarities of some specific stone samples of Leilatepe culture were found in the sites of Maikop culture.